Vegetable-derived bioactive nitrate and cardiovascular health. - Bondonno, C.; Blekkenhorst, L.; Liu, A.; Bondonno, N.; Ward, Natalie; Croft, K.; Hodgson, J. (2017)
Vegetable derived nitrate is now recognised as an important bioactive phytochemical with cardioprotective properties. Nitrate, through the recently described enterosalivary nitrate-nitrite-nitric oxide (NO) pathway, increases NO, a molecule pivotal for cardiovascular health. Clinical trials have observed that dietary nitrate has similar effects to NO when supplied exogenously. These effects include reduced blood pressure and improvements in other markers of vascular health such as endothelial function, arterial stiffness, ischemia reperfusion injury, blood flow, and platelet aggregation. Few observational studies, however, have examined dietary nitrate intake and long term cardiovascular health outcomes. This represents a significant gap in the literature. There is also a lingering concern about a possible carcinogenic effect of nitrate intake. Additionally, a number of potential factors that could impact nitrate to nitrite to NO reduction have been identified. This review will provide an overview of the evidence to date that nitrate, through its effects on endogenous NO and vascular health, is an important bioactive cardioprotective component of a diet rich in vegetables.